Comparison of Polymerase Chain Reaction and Histopathology for the Detection of Helicobacter pylori in Gastric Biopsies - Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
.